Journal of Numerical Mathematics (De Gruyter, 2001)
The Journal of Numerical Mathematics contains high-quality papers featuring contemporary research in all areas of Numerical Mathematics. This includes the development, analysis, and implementation of new and innovative methods in Numerical Linear Algebra, Numerical Analysis, Optimal Control/Optimization, and Scientific Computing.